Self-healing rubber asphalt based on solid waste aggregate and preparation process thereof
By adding desulfurization rubber powder, asphalt modifier, microcapsules, tackifying resin, nanofillers and solid waste aggregates to rubber asphalt, the problem of fatigue cracking in existing rubber asphalt pavement is easily encountered under the changes in strain stress, and the self-healing and fatigue resistance improvement is achieved.
Patent Information
- Application Number
- CN202411979574.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing rubber asphalt pavement is prone to fatigue cracking under long-term strain stress changes, resulting in cracking, cracking, looseness and depression of the road surface, making it difficult to meet the fatigue resistance requirements of the current road environment.
Self-healing rubber asphalt based on solid waste aggregates is used, and its formulation includes matrix asphalt, desulfurization rubber powder, asphalt modifier, microcapsules, tackifying resin, nanofillers, solid waste aggregates and mineral powder. Through the combination of these raw materials, the self-healing ability and fatigue resistance of rubber asphalt are improved.
The self-healing effect of rubber asphalt is achieved, improving its performance and fatigue resistance at high and low temperatures, and extending the service life of the road surface.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rubber asphalt, and in particular to a self-healing rubber asphalt based on solid waste aggregate and a preparation process thereof. Background Art
[0002] With the increase in highway mileage, road loads are also increasing year by year. The traffic volume of heavy trucks is increasing rapidly. The extremely heavy vehicle load is causing more and more serious damage to the road surface, which has caused many problems with asphalt pavements. During the service of the pavement, it will be affected by factors such as ambient temperature changes and vehicle loads. The strain stress will change irregularly and repeatedly for a long time, which will cause the strength of the entire pavement structure to gradually weaken. Under the repeated action of loads, the pavement will suffer from fatigue cracking, and eventually lead to cracking, cracking, loosening and depression of the pavement. Fatigue damage cracking is a common disease of the pavement at present, and it is also a problem that needs to be solved urgently in highway construction.
[0003] Rubber is a common modifier in base asphalt. Asphalt pavement mixed with rubber powder has excellent anti-fatigue properties. The raw material of rubber powder comes from waste tires. Waste tires are industrial hazardous solid wastes. They have strong heat resistance, mechanical resistance, corrosion resistance, and are extremely difficult to degrade. Rubber asphalt pavement has better viscosity and better elastic recovery ability than conventional asphalt, but its mixture anti-fatigue performance still cannot meet the requirements of the current road environment. Summary of the invention
[0004] In order to solve the problems in the prior art, the present invention provides a self-healing rubber asphalt based on solid waste aggregate and a preparation process thereof.
[0005] The first object of the present invention is to provide a self-healing rubber asphalt based on solid waste aggregate, using the following technical solution:
[0006] A self-healing rubber asphalt based on solid waste aggregates, the rubber asphalt comprising the following raw materials in parts by weight: 30-45 parts of base asphalt, 8-15 parts of desulfurized rubber powder, 1.5-2.6 parts of asphalt modifier, 1-2.2 parts of microcapsules, 3-7 parts of tackifying resin, 6-11 parts of nanofiller, 130-150 parts of solid waste aggregates, and 12-15 parts of mineral powder.
[0007] By adopting the above-mentioned technical scheme, after adding desulfurized rubber powder, asphalt modifier, microcapsule, thickening resin and nanofiller to the base asphalt, the present application can not only ensure the self-healing effect of rubber asphalt, but also the addition of microcapsule powder can achieve a long-term self-repair effect. Moreover, the combined use of asphalt modifier and thickening resin can effectively improve its bonding ability with solid waste aggregates, and the addition of mineral powder can fill the gaps between solid waste aggregates, thereby ensuring the density of the asphalt pavement and improving the fatigue resistance of the asphalt pavement.
[0008] In a preferred embodiment, the microcapsules are obtained by the following preparation method:
[0009] (1) adding sodium alginate into water and stirring to dissolve to form a sodium alginate solution with a concentration of 1.2-2.5 wt %;
[0010] (2) adding expanded perlite powder to the sodium alginate solution, and shearing for 20-30 min at a rotation speed of 4000-5000 r / min to form a suspension, wherein the expanded perlite powder is 0.4-2.5 times the dry weight of the sodium alginate;
[0011] (3) mixing the asphalt regeneration agent and the surfactant at a temperature of 40-50° C. and stirring for 10-15 minutes to form a mixture;
[0012] (4) adding the mixture obtained in step (2) to the suspension of step (2), and shearing for 5-10 min at a temperature of 40-50° C. and a rotation speed of 14000-15000 r / min to obtain a mixed solution, wherein the asphalt regeneration agent is 10% of the sodium alginate solution, and the surfactant is 5% of the asphalt regeneration agent content;
[0013] (5) The mixed solution is dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 12-13 hours to form capsules. The capsules are rinsed with clean water and dried at room temperature to form microcapsules.
[0014] Since calcium alginate capsules with a single wall material have the disadvantages of poor stability and low mechanical strength, during the drying process, the capsule volume shrinks due to water volatilization, and the capsule will produce obvious sudden release or burst release of asphalt regeneration agent, resulting in early release or one-time release of asphalt regeneration agent, thereby affecting the self-healing performance of asphalt. After adopting the above technical solution, this application uses sodium alginate and expanded perlite powder as capsule wall materials to synergistically improve the strength and flexibility of microcapsules. At the same time, the special structure of expanded perlite can increase the effective adsorption of asphalt regeneration agent in the wall material, which can achieve the effect of slow release of asphalt regeneration agent and achieve a longer self-healing effect, thereby extending the service life of asphalt pavement.
[0015] In a preferred embodiment, in the step (5), nano-titanium dioxide is added to the mixed solution and stirred to disperse evenly, then dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 12-13 hours to form capsules, and the capsules are rinsed with clean water and dried at room temperature to form microcapsules, and the amount of nano-titanium dioxide added is 1.1-1.3% of the weight of the expanded perlite powder.
[0016] By adopting the above technical scheme, after adding nano titanium dioxide to the sodium alginate solution, it can have a certain sealing effect on the wall material, reduce the leakage of the asphalt regeneration agent, and improve the utilization effect of the asphalt regeneration agent. At the same time, when the addition amount of nano titanium dioxide is limited to 1.1-1.3% of the weight of the expanded perlite powder, it can not only effectively block the micropores on the surface of the microcapsule, but also reduce its influence on the adsorption performance of the expanded perlite powder on the asphalt regeneration agent.
[0017] In a preferred embodiment, the surfactant is Tween 80.
[0018] In a preferred embodiment, the asphalt modifier is obtained by mixing 30-40 parts by weight of SBS, 18-22 parts by weight of petroleum resin, 1-2 parts by weight of antioxidant, and 0.5-1.5 parts by weight of polyamide, followed by melt extrusion and granulation.
[0019] By adopting the above technical solution, after the asphalt modifier is composed of SBS, petroleum asphalt, antioxidant and polyamide, it has high solubility in the base asphalt and good viscoelastic properties, which can effectively improve the fatigue resistance of the asphalt pavement.
[0020] In a preferred embodiment, the nanofiller is organic montmorillonite, and the organic montmorillonite is obtained by the following preparation method:
[0021] S1. Add melamine and 2,3-epoxypropyltrimethylammonium chloride in a molar ratio of 1:6 into water, and add a catalyst at the same time, react at 90° C. for 12 h to obtain a reaction mixture, let the reaction mixture stand, filter, and then dry to obtain a powder;
[0022] S2. Add the powder and montmorillonite obtained in step S1 into water, and ultrasonically disperse for 30 minutes. Stir and react at 80±2° C. for 4 hours, then stand, filter, and dry to obtain organic montmorillonite. The amount of the powder added is 10-30% of the weight of the montmorillonite.
[0023] By adopting the above technical scheme, the nanofiller adopts organic montmorillonite, which can effectively improve the low-temperature performance of asphalt pavement. At the same time, after the montmorillonite is modified by an intercalating agent made of melamine and 2,3-epoxypropyltrimethylammonium chloride, the interlamellar spacing of the montmorillonite is significantly increased. The increase in the interlamellar spacing can form an intercalation structure between the asphalt modifier, the thickening resin, and the matrix asphalt molecules, so that the asphalt modifier and the thickening resin are more fully dispersed in the asphalt, so that the asphalt modifier, the thickening resin, etc. can play a better role, and the buffer system of the asphalt pavement under stress can be more stable, and the deformation recovery performance is more superior. In addition, the addition of organic montmorillonite can stabilize the role of the asphalt modifier in the asphalt, and promote the asphalt modifier to better play its low-temperature modification ability. However, when the content of organic montmorillonite exceeds a certain range, the ductility of the asphalt decreases, indicating that the excessive addition of organic montmorillonite leads to particle agglomeration, which weakens its effect on the low-temperature modification of asphalt.
[0024] In a preferred embodiment, the tackifying resin is composed of polystyrene maleic anhydride resin and alkylphenol-formaldehyde resin in a weight ratio of 1:1.
[0025] By adopting the above technical scheme, the addition of polystyrene maleic anhydride resin and alkylphenol formaldehyde resin can effectively bond the raw materials together, so that the obtained high-viscosity modified asphalt has good viscoelasticity. In addition, since the resin can reduce the surface free energy of the binder, the contact angle between the asphalt and the aggregate surface is reduced, and the viscosity is increased by surface diffusion and internal penetration and reaction with the asphalt, so that the adhesion between the asphalt and the aggregate surface is further increased, which can not only improve the bonding ability between the matrix asphalt and the solid waste aggregate, reduce the probability of separation of the solid waste aggregate and the asphalt after the asphalt pavement is used for a long time, and improve the service life of the asphalt pavement, at the same time, the addition of polystyrene maleic anhydride resin and alkylphenol formaldehyde resin, and its combination with desulfurized rubber powder, can effectively resist the deformation of the asphalt pavement at high temperature, improve the high temperature stability of the asphalt, and at the same time reduce the brittleness of the asphalt at low temperature, so that the rubber asphalt has a certain low temperature flexibility and improves the crack resistance.
[0026] In a preferred embodiment, the rubber asphalt further comprises 3-6 parts by weight of polyphosphoric acid.
[0027] By adopting the above technical solution, the combination of polyphosphoric acid and desulfurized rubber powder can effectively improve the high and low temperature performance and fatigue resistance of asphalt mixture. The reason may be that the phosphate groups in the polyphosphoric acid molecules can chemically react with the desulfurized rubber powder to form a cross-linked structure. This cross-linking can enhance the cohesion and adhesion of rubber asphalt, thereby improving the mechanical properties and durability of rubber asphalt. At the same time, under high temperature conditions, polyphosphoric acid chemically reacts with the components in the asphalt to form a more stable structure, which effectively improves the high and low temperature performance of rubber asphalt and extends the service life of rubber asphalt pavement.
[0028] The second aspect of the present invention is to provide a preparation process of the self-healing rubber asphalt based on solid waste aggregate as described above, comprising the following steps:
[0029] S1, in the preparatory stage, the desulfurized rubber powder is activated at 180-210°C for standby use;
[0030] S2, after melting the matrix asphalt at a temperature of 160-170° C., add the desulfurized rubber powder, asphalt modifier and tackifying resin activated in step S1, and stir at a speed of 3000-4000 r / min for 20-25 min;
[0031] S3. Add microcapsules, nanofillers, solid waste aggregates, mineral powder and 3-6 parts by weight of polyphosphoric acid to step S2, and continue stirring at a rotation speed of 3000-4000 r / min for 30-40 minutes to obtain rubber asphalt.
[0032] In a preferred embodiment, the nanofiller is heated at 130-140° C. for 30 min and then added into step S3.
[0033] By adopting the above technical solution, the present application heats the nanofiller and then adds it to the matrix asphalt, which can effectively reduce the agglomeration of the nanofiller in the matrix asphalt, so that the filler can be effectively dispersed in the matrix asphalt.
[0034] In summary, the present invention has the following beneficial effects: the combined use of the raw materials in the present application effectively improves the self-healing ability of the rubber asphalt, and also makes the rubber asphalt have good high and low temperature performance and softness, thereby effectively improving the fatigue resistance of the rubber asphalt. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below with reference to the embodiments.
[0036] Asphalt is generally composed of four parts: bitumen, colloid, saturated components and aromatic components. During the actual use of asphalt pavement, asphalt ages due to natural conditions such as temperature and oxidation. From the component point of view, the content of saturated components and aromatic components in asphalt decreases, and the asphalt increases, making the asphalt brittle and hard, and prone to cracks during vehicle driving. Asphalt regeneration can be regarded as the reverse process of aging. If light components can be added to the asphalt to make up for the part lost during the aging process of asphalt, the self-repairing properties of asphalt can be enhanced to a certain extent. The regeneration agent contains more saturated components and aromatic components. After mixing with asphalt, it can improve the rheological properties of aged asphalt and restore its performance.
[0037] Solid waste aggregate includes coarse aggregate and fine aggregate. The fine aggregate accounts for 60% of the total solid waste aggregate. The crushing value of coarse aggregate is 9%, the apparent relative density is 2.567%, the water absorption rate is 0.2%, and the content of needle-like particles is 5%. The apparent relative density of fine aggregate is 2.681, the mud content (the content of particles less than 0.075mm) is 1.2%, and the sand equivalent is 60%.
[0038] Preparation Example 1.1
[0039] A method for preparing microcapsules comprises the following steps:
[0040] (1) adding sodium alginate into water and stirring to dissolve to form a sodium alginate solution with a concentration of 1.2 wt %;
[0041] (2) adding expanded perlite powder to the sodium alginate solution and shearing for 30 min at a rotation speed of 4000 r / min to form a suspension, wherein the expanded perlite powder is 0.4 times the dry weight of the sodium alginate;
[0042] (3) mixing the asphalt regeneration agent and Tween 80 at a temperature of 40° C. and stirring for 10 minutes to form a mixture;
[0043] (4) adding the mixture obtained in step (2) to the suspension of step (2), and shearing for 5 min at a temperature of 40° C. and a rotation speed of 14,000 r / min to obtain a mixed solution, wherein the asphalt regeneration agent is 10% by weight of the sodium alginate solution, and the amount of Tween 80 added is 5% by weight of the asphalt regeneration agent;
[0044] (5) The mixed solution was dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 12 hours to form capsules. The capsules were rinsed with clean water and dried at room temperature to form microcapsules.
[0045] Preparation Example 1.2
[0046] A method for preparing microcapsules comprises the following steps:
[0047] (1) adding sodium alginate into water and stirring to dissolve to form a sodium alginate solution with a concentration of 2.0 wt %;
[0048] (2) adding expanded perlite powder to the sodium alginate solution and shearing for 30 min at a rotation speed of 0.000 r / min to form a suspension, wherein the expanded perlite powder is 1.5 times the dry weight of the sodium alginate;
[0049] (3) mixing the asphalt regeneration agent and Tween 80 at a temperature of 50° C. and stirring for 15 minutes to form a mixture;
[0050] (4) adding the mixture obtained in step (2) to the suspension of step (2), and shearing for 10 min at a temperature of 40° C. and a rotation speed of 14000 r / min to obtain a mixed solution, wherein the asphalt regeneration agent is 10% by weight of the sodium alginate solution, and the amount of Tween 80 added is 5% by weight of the asphalt regeneration agent;
[0051] (5) The mixed solution was dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 12 hours to form capsules. The capsules were rinsed with clean water and dried at room temperature to form microcapsules.
[0052] Preparation Example 1.3
[0053] A method for preparing microcapsules comprises the following steps:
[0054] (1) adding sodium alginate into water and stirring to dissolve to form a sodium alginate solution with a concentration of 2.5 wt %;
[0055] (2) adding expanded perlite powder to the sodium alginate solution and shearing for 30 min at a rotation speed of 5000 r / min to form a suspension, wherein the expanded perlite powder is 2.5 times the dry weight of the sodium alginate;
[0056] (3) mixing the asphalt regeneration agent and Tween 80 at a temperature of 50° C. and stirring for 10 minutes to form a mixture;
[0057] (4) adding the mixture obtained in step (2) to the suspension of step (2), and shearing for 10 min at a temperature of 40° C. and a rotation speed of 15,000 r / min to obtain a mixed solution, wherein the asphalt regeneration agent is 10% by weight of the sodium alginate solution, and Tween 80 is 5% by weight of the asphalt regeneration agent;
[0058] (5) The mixed solution was dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 13 hours to form capsules. The capsules were rinsed with clean water and dried at room temperature to form microcapsules.
[0059] Preparation Example 1.4
[0060] A method for preparing microcapsules, which is different from Preparation Example 1.2 in that, in step (5), nano-titanium dioxide is added to the mixed solution and stirred for 15 minutes, then dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 12 hours to form capsules, and the capsules are rinsed with clean water and dried at room temperature to form microcapsules, wherein the amount of nano-titanium dioxide added is 1.1% of the weight of the expanded perlite powder, and the rest is the same as Preparation Example 1.2.
[0061] Preparation Example 1.5
[0062] A method for preparing microcapsules, which is different from Preparation Example 1.2 in that, in step (5), nano-titanium dioxide is added to the mixed solution and stirred for 15 minutes, then dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 12 hours to form capsules, and the capsules are rinsed with clean water and dried at room temperature to form microcapsules, wherein the amount of nano-titanium dioxide added is 1.2% by weight of the expanded perlite powder, and the rest is the same as Preparation Example 1.2.
[0063] Preparation Example 1.6
[0064] A method for preparing microcapsules, which is different from Preparation Example 1.2 in that, in step (5), nano-titanium dioxide is added to the mixed solution and stirred for 15 minutes, then dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 12 hours to form capsules, and the capsules are rinsed with clean water and dried at room temperature to form microcapsules, wherein the amount of nano-titanium dioxide added is 1.3% of the weight of the expanded perlite powder, and the rest is the same as Preparation Example 1.2.
[0065] Comparative Preparation Example 1.1
[0066] A method for preparing microcapsules, which is different from Preparation Example 1.2 in that an equal amount of attapulgite is used to replace expanded perlite powder, and the rest is the same as Preparation Example 1.2.
[0067] Preparation Example 2.1
[0068] A method for preparing an asphalt modifier comprises the following steps: 300 g of SBS, 180 g of petroleum resin, 10 g of an antioxidant and 5 g of polyamide are mixed, and then melt-extruded and granulated to obtain the asphalt modifier.
[0069] Preparation Example 2.2
[0070] A method for preparing an asphalt modifier comprises the following steps: mixing 350 g of SBS, 200 g of petroleum resin, 15 g of an antioxidant and 10 g of polyamide, and then melt-extruding and granulating the mixture to obtain the asphalt modifier.
[0071] Preparation Example 2.3
[0072] A method for preparing an asphalt modifier comprises the following steps: mixing 400 g of SBS, 220 g of petroleum resin, 20 g of an antioxidant and 15 g of polyamide, and then melt-extruding and granulating the mixture to obtain the asphalt modifier.
[0073] Preparation Example 3.1
[0074] A method for preparing an organic montmorillonite comprises the following steps:
[0075] S1. Add melamine and 2,3-epoxypropyltrimethylammonium chloride in a molar ratio of 1:6 into water, and add a catalyst at the same time, react at 90° C. for 12 h to obtain a reaction mixture, let the reaction mixture stand, filter, and then dry to obtain a powder;
[0076] S2. Add the powder and montmorillonite obtained in step S1 into water, and ultrasonically disperse for 30 minutes. Stir and react at 80±2° C. for 4 hours, then stand, filter, and dry to obtain organic montmorillonite. The amount of the powder added is 10% of the weight of the montmorillonite.
[0077] Preparation Example 3.2
[0078] A method for preparing an organic montmorillonite comprises the following steps:
[0079] S1. Add melamine and 2,3-epoxypropyltrimethylammonium chloride in a molar ratio of 1:6 into water, and add a catalyst at the same time, react at 90° C. for 12 h to obtain a reaction mixture, let the reaction mixture stand, filter, and then dry to obtain a powder;
[0080] S2. Add the powder and montmorillonite obtained in step S1 into water, and ultrasonically disperse for 30 minutes. Stir and react at 80±2° C. for 4 hours, then stand, filter, and dry to obtain organic montmorillonite. The amount of the powder added is 20% of the weight of the montmorillonite.
[0081] Preparation Example 3.3
[0082] A method for preparing an organic montmorillonite comprises the following steps:
[0083] S1. Add melamine and 2,3-epoxypropyltrimethylammonium chloride in a molar ratio of 1:6 into water, and add a catalyst at the same time, react at 90° C. for 12 h to obtain a reaction mixture, let the reaction mixture stand, filter, and then dry to obtain a powder;
[0084] S2. Add the powder and montmorillonite obtained in step S1 into water, and ultrasonically disperse for 30 minutes. Stir and react at 80±2° C. for 4 hours, then stand, filter, and dry to obtain organic montmorillonite. The amount of the powder added is 30% of the weight of the montmorillonite.
[0085] Example 1
[0086] A preparation process of self-healing rubber asphalt based on solid waste aggregates, comprising the following steps:
[0087] S1, in the preparatory stage, 0.8 kg of desulfurized rubber powder is activated at 180°C for standby use;
[0088] S2, melt 3 kg of 70# matrix asphalt at 160°C, add the desulfurized rubber powder activated in step S1, 0.15 kg of the asphalt modifier obtained in Preparation Example 2.1, and 0.3 kg of tackifying resin, and stir at a speed of 3000 r / min for 25 min, wherein the tackifying resin is composed of polystyrene maleic anhydride resin and alkylphenol-formaldehyde resin in a weight ratio of 1:1;
[0089] S3. Add 0.1 kg of microcapsules obtained in Preparation Example 1.1, 0.6 kg of organic montmorillonite obtained in Preparation Example 3.1, 13 kg of solid waste aggregates, and 1.2 kg of mineral powder into step S2, and stir at a rotation speed of 300 r / min for 30 minutes to obtain rubber asphalt.
[0090] Example 2
[0091] A preparation process of self-healing rubber asphalt based on solid waste aggregates, comprising the following steps:
[0092] S1, in the preparatory stage, 1.2 kg of desulfurized rubber powder is activated at 180°C for standby use;
[0093] S2, after melting 3.8 kg of 70# matrix asphalt at a temperature of 160°C, add the desulfurized rubber powder activated in step S1, 0.21 kg of the asphalt modifier obtained in Preparation Example 2.1, and 0.5 kg of tackifying resin, and stir at a speed of 3000 r / min for 20 min, wherein the tackifying resin is composed of polystyrene maleic anhydride resin and alkylphenol-formaldehyde resin in a weight ratio of 1:1;
[0094] S3. Add 0.17 kg of microcapsules prepared in Preparation Example 1.1, 0.9 kg of organic montmorillonite obtained in Preparation Example 3.1, 14 kg of solid waste aggregates, and 1.3 kg of mineral powder into step S2, and stir at a rotation speed of 3000 r / min for 30 minutes to obtain rubber asphalt.
[0095] Example 3
[0096] A preparation process of self-healing rubber asphalt based on solid waste aggregates, comprising the following steps:
[0097] S1, in the preparatory stage, 1.5 kg of desulfurized rubber powder is activated at 180°C for standby use;
[0098] S2, after melting 4.5kg 70# matrix asphalt at a temperature of 160°C, adding the desulfurized rubber powder activated in step S1, 0.26kg asphalt modifier, and 0.7kg tackifying resin, and stirring at a speed of 3000r / min for 20min, wherein the tackifying resin is composed of polystyrene maleic anhydride resin and alkyl phenolic resin in a weight ratio of 1:1;
[0099] S3. Add 0.22 kg of the microcapsules prepared in Preparation Example 1.1, 1.1 kg of the organic montmorillonite obtained in Preparation Example 3.1, 15 kg of solid waste aggregates, and 1.5 kg of mineral powder into step S2, and stir at a rotation speed of 3000 r / min for 30 minutes to obtain rubber asphalt.
[0100] Example 4
[0101] A preparation process of self-healing rubber asphalt based on solid waste aggregates, comprising the following steps:
[0102] S1, in the preparatory stage, 1.2 kg of desulfurized rubber powder is activated at 210°C for standby use;
[0103] S2, after melting 3.8 kg of 70# matrix asphalt at a temperature of 170°C, add the desulfurized rubber powder activated in step S1, 0.21 kg of the asphalt modifier obtained in Preparation Example 2.1, and 0.5 kg of tackifying resin, and stir at a speed of 4000 r / min for 25 min, wherein the tackifying resin is composed of polystyrene maleic anhydride resin and alkylphenol-formaldehyde resin in a weight ratio of 1:1;
[0104] S3. Add 0.17 kg of microcapsules prepared in Preparation Example 1.1, 0.9 kg of organic montmorillonite obtained in Preparation Example 3.1, 14 kg of solid waste aggregates, and 1.3 kg of mineral powder into step S2, and stir at a rotation speed of 4000 r / min for 40 minutes to obtain rubber asphalt.
[0105] Example 5
[0106] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 2 in that the organic montmorillonite obtained in Preparation Example 3.1 is heated at 130°C for 30 minutes and then added in step S3, and the rest is the same as Example 2.
[0107] Example 6
[0108] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 2 in that the organic montmorillonite obtained in Preparation Example 3.1 is heated at 140°C for 30 minutes and then added in step S3, and the rest is the same as Example 2.
[0109] Example 7
[0110] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 5 in that the microcapsules are the microcapsules obtained in Preparation Example 1.2, the asphalt modifier is the asphalt modifier obtained in Preparation Example 2.2, and the organic montmorillonite is the organic montmorillonite obtained in Preparation Example 3.2, and the rest are the same as Example 5.
[0111] Example 8
[0112] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 5 in that the microcapsules are the microcapsules obtained in Preparation Example 1.3, the asphalt modifier is the asphalt modifier obtained in Preparation Example 2.2, and the organic montmorillonite is the organic montmorillonite obtained in Preparation Example 3.2, and the rest are the same as Example 5.
[0113] Example 9
[0114] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 5 in that the microcapsules are the microcapsules obtained in Preparation Example 1.4, the asphalt modifier is the asphalt modifier obtained in Preparation Example 2.2, and the organic montmorillonite is the organic montmorillonite obtained in Preparation Example 3.2, and the rest are the same as Example 5.
[0115] Example 10
[0116] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 5 in that the microcapsules are the microcapsules obtained in Preparation Example 1.5, the asphalt modifier is the asphalt modifier obtained in Preparation Example 2.2, and the organic montmorillonite is the organic montmorillonite obtained in Preparation Example 3.2, and the rest are the same as Example 5.
[0117] Embodiment 11
[0118] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 5 in that the microcapsules are the microcapsules obtained in Preparation Example 1.6, the asphalt modifier is the asphalt modifier obtained in Preparation Example 2.2, and the organic montmorillonite is the organic montmorillonite obtained in Preparation Example 3.2, and the rest are the same as Example 5.
[0119] Example 12
[0120] A preparation process of self-healing rubber asphalt based on solid waste aggregates, which is different from Example 5 in that the microcapsules are the microcapsules obtained in Preparation Example 1.5, the asphalt modifier is the asphalt modifier obtained in Preparation Example 2.3, and the organic montmorillonite is the organic montmorillonite obtained in Preparation Example 3.3, and the rest are the same as Example 5.
[0121] Embodiment 13
[0122] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 10 in that 0.3 kg of polyphosphoric acid is added to step S2, and the rest is the same as Example 10.
[0123] Embodiment 14
[0124] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 10 in that 0.5 kg of polyphosphoric acid is added to step S2, and the rest is the same as Example 10.
[0125] Embodiment 15
[0126] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 10 in that 0.6 kg of polyphosphoric acid is added to step S2, and the rest is the same as Example 10.
[0127] Example 16
[0128] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 2 in that an equal amount of SBS modifier is used as the asphalt modifier instead of the asphalt modifier obtained in Preparation Example 2.1, and the rest are the same as Example 2.
[0129] Embodiment 17
[0130] A preparation process of self-healing rubber asphalt based on solid waste aggregate is different from that of Example 2 in that only alkyl phenol-formaldehyde resin is used as the tackifying resin, and the rest are the same as those of Example 2.
[0131] Embodiment 18
[0132] A preparation process of self-healing rubber asphalt based on solid waste aggregate is different from that of Example 2 in that the tackifying resin only uses polystyrene maleic anhydride resin, and the rest is the same as that of Example 2.
[0133] Embodiment 19
[0134] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 2 in that the tackifying resin is composed of polystyrene maleic anhydride resin and terpene resin in a weight ratio of 1:1, and the rest is the same as Example 2.
[0135] Embodiment 20
[0136] A preparation process of self-healing rubber asphalt based on solid waste aggregate, which is different from Example 2 in that the organic montmorillonite adopts commercially available alkyl quaternary ammonium salt modified high-purity montmorillonite with a specific gravity of 1.8 g / cm 3 , Bulk density <0.3g / cm 3 , the rest are the same as in Example 2.
[0137] Embodiment 21
[0138] A preparation process of self-healing rubber asphalt based on solid waste aggregates, which is different from Example 2 in that an equal amount of nano-silicon dioxide is used to replace the organic montmorillonite obtained in Preparation Example 3.1, and the rest is the same as Example 2.
[0139] Comparative Example 1
[0140] A preparation process of self-healing rubber asphalt based on solid waste aggregates, which is different from Example 2 in that organic montmorillonite is missing in the raw materials, and the rest is the same as Example 2.
[0141] Comparative Example 2
[0142] A preparation process of self-healing rubber asphalt based on solid waste aggregates, which is different from Example 2 in that the microcapsules use the microcapsules obtained in Comparative Preparation Example 1.1, and the rest are the same as Example 2.
[0143] Comparative Example 3
[0144] A preparation process of self-healing rubber asphalt based on solid waste aggregates, which is different from Example 2 in that there is no tackifying resin in the raw materials, and the rest is the same as Example 2.
[0145] Performance Testing
[0146] The softening point, ductility, self-healing performance and fatigue resistance of the rubber asphalt obtained in the above embodiments and preparation examples were tested. The test results are shown in Table 1.
[0147] The self-healing performance is based on the fatigue self-healing percentage. According to the four-point bending fatigue test in T0739-2011, a strain control valve is used to perform fatigue tests on asphalt mixture specimens at 500 microstrain and 15°C. After fatigue damage, the specimens are placed in a 50°C constant temperature box for healing and curing for 4 hours, and then kept at 15°C for 24 hours. Fatigue tests are then carried out under the same conditions. The ratio of the fatigue life after healing to the initial fatigue life is the self-healing percentage.
[0148] The fatigue resistance test was carried out in accordance with the relevant provisions of T0739-2011 "Four-point bending fatigue life test of asphalt mixture". The asphalt mixture specimens were subjected to fatigue tests under the conditions of 500 microstrain and 15°C. The test termination condition was the number of loading cycles corresponding to the bending stiffness modulus being reduced to 50% of the initial bending stiffness modulus.
[0149] Softening point test: Place the asphalt mixture sample obtained above in a metal ring, place a steel ball on it, place it in 5℃ water, and heat it at a rate of 5±0.5℃ / min until the steel ball sinks to 25.4mm. The temperature of the asphalt mixture is recorded as the softening point. The higher the softening point, the more resistant the asphalt mixture is to high temperatures.
[0150] Ductility test: used to detect plasticity. Specifically, the asphalt mixture sample is made into an 8-shaped standard specimen, and stretched to the length (cm) at the breaking speed of 50 mm per minute at a temperature of 10°C. The higher the ductility, the better the plasticity of the asphalt mixture. The prepared asphalt sample is not easy to break at low temperature and has strong crack resistance.
[0151] Table 1 Rubber asphalt mixture test results
[0152] project Softening point / ℃ Elongation / cm Self-healing rate / % Fatigue life / times Example 1 81 32 70 91765 Example 2 84 33 73 93654 Example 3 83 33 72 93425 Example 4 84 32 73 93586 Example 5 86 33 75 97876 Example 6 86 33 74 97251 Example 7 87 36 79 100789 Example 8 85 33 77 99673 Example 9 90 37 81 102745 Example 10 92 40 85 105761 Embodiment 11 89 38 83 105324 Example 12 91 40 85 105476 Embodiment 13 93 40 85 106863 Embodiment 14 94 42 85 107987 Embodiment 15 94 42 85 107764 Example 16 76 28 71 90965 Embodiment 17 78 29 70 89896 Embodiment 18 79 29 70 89126 Embodiment 19 81 30 71 91432 Embodiment 20 80 29 71 90589 Embodiment 21 80 29 70 91435 Comparative Example 1 74 26 68 88542 Comparative Example 2 77 28 65 89587 Comparative Example 3 75 26 70 85321
[0153] From the table above we can see that:
[0154] The softening point of the rubber asphalt mixture obtained in Examples 1-15 of the present application is above 80°C, the ductility is 32 cm or more, the self-healing rate is 70% or more, and the fatigue life is more than 90,000 times, indicating that the rubber asphalt mixture obtained in the present application not only has good self-healing ability, but also has good high and low temperature performance and fatigue resistance.
[0155] Compared with Example 2, when only SBS modifier is used as the asphalt modifier, the softening point and ductility of the asphalt mixture obtained in Example 16 are significantly reduced, the self-healing rate is slightly reduced but the change is not large, and the fatigue life is also significantly reduced. It can be seen that the asphalt modifier prepared by the present application can effectively improve the high and low temperature performance and fatigue resistance of asphalt.
[0156] Compared with Example 2, when the tackifying resin is only polystyrene maleic anhydride resin or alkyl phenolic resin, the high and low temperature performance and fatigue resistance of the rubber asphalt mixture obtained in Examples 17-18 are significantly reduced; when Example 19 is compared with Example 2, when the tackifying resin is composed of polystyrene maleic anhydride resin and terpene resin, the various properties of the rubber asphalt mixture obtained in Example 19 are slightly lower than the properties of the rubber asphalt mixture obtained in Example 2, which can further illustrate that the combined use of two tackifying resins in the present application can effectively improve the various properties of the asphalt mixture.
[0157] Compared with Example 2, when commercially available organic montmorillonite or nano-silicon dioxide is used instead of the organic montmorillonite obtained in Preparation Example 3.1, the low temperature performance and fatigue life of the rubber asphalt mixture obtained in Examples 20-21 are significantly reduced, indicating that the combined use of various raw materials in the present application effectively improves the various properties of the rubber asphalt mixture.
[0158] Compared with Example 2, the softening point, ductility, self-healing rate and fatigue life of the asphalt mixture obtained in Comparative Examples 1-3 are significantly reduced. It can be seen that the combination of the raw materials in the present application effectively ensures the high and low temperature performance, self-healing performance and anti-fatigue performance of the rubber asphalt mixture.
[0159] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, all equivalent changes made according to the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A self-healing rubber asphalt based on solid waste aggregate, characterized by: The rubber asphalt comprises the following raw materials in parts by weight: 30-45 parts of base asphalt, 8-15 parts of desulfurized rubber powder, 1.5-2.6 parts of asphalt modifier, 1-2.2 parts of microcapsules, 3-7 parts of tackifying resin, 6-11 parts of nano filler, 130-150 parts of solid waste aggregate, and 12-15 parts of mineral powder.
2. The self-healing rubber asphalt based on solid waste aggregate according to claim 1, characterized in that: The microcapsules are prepared by the following method: (1) adding sodium alginate into water and stirring to dissolve to form a sodium alginate solution with a concentration of 1.2-2.5 wt%; (2) adding expanded perlite powder to the sodium alginate solution, and shearing for 20-30 minutes at a rotation speed of 4000-5000 r / min to form a suspension, wherein the expanded perlite powder is 0.4-2.5 times the dry weight of the sodium alginate; (3) Mixing the asphalt regeneration agent and the surfactant at a temperature of 40-50°C and stirring for 10-15 minutes to form a mixture; (4) adding the mixture obtained in step (2) to the suspension of step (2), and shearing for 5-10 min at a temperature of 40-50° C. and a rotation speed of 14000-15000 r / min to obtain a mixed solution, wherein the asphalt regeneration agent is 10% of the sodium alginate solution, and the surfactant is 5% of the asphalt regeneration agent; (5) The mixed solution was dropped into a calcium chloride solution with a mass concentration of 2.5% and reacted for 12-13 hours to form capsules. The capsules were rinsed with clean water and dried at room temperature to form microcapsules.
3. The self-healing rubber asphalt based on solid waste aggregate according to claim 2, characterized in that: In the step (5), nano titanium dioxide is added to the mixed solution and stirred to disperse evenly, and then dropped into a calcium chloride solution with a mass concentration of 2.5% to react for 12-13 hours to form capsules. The capsules are rinsed with clean water and dried at room temperature to form microcapsules. The amount of nano titanium dioxide added is 1.1-1.3% of the weight of the expanded perlite powder.
4. The self-healing rubber asphalt based on solid waste aggregate according to claim 2, characterized in that: The surfactant used is Tween 80.
5. The self-healing rubber asphalt based on solid waste aggregate according to claim 1, characterized in that: The asphalt modifier is obtained by mixing 30-40 parts by weight of SBS, 18-22 parts by weight of petroleum resin, 1-2 parts by weight of antioxidant and 0.5-1.5 parts by weight of polyamide, and then melt-extruding and granulating.
6. The self-healing rubber asphalt based on solid waste aggregate according to claim 1, characterized in that: The nano filler is organic montmorillonite, which is prepared by the following method: S1, adding melamine and 2,3-epoxypropyltrimethylammonium chloride in a molar ratio of 1:6 into water, adding a catalyst at the same time, reacting at 90° C. for 12 h to obtain a reaction mixture, allowing the reaction mixture to stand, filtering, and drying to obtain a powder; S2. Add the powder and montmorillonite obtained in step S1 into water, and ultrasonically disperse for 30 minutes. Stir and react at 80±2° C. for 4 hours, then stand, filter, and dry to obtain organic montmorillonite. The amount of the powder added is 10-30% of the weight of the montmorillonite.
7. The self-healing rubber asphalt based on solid waste aggregate according to claim 1, characterized in that: The tackifying resin is composed of polystyrene maleic anhydride resin and alkylphenol-formaldehyde resin in a weight ratio of 1:
1.
8. The self-healing rubber asphalt based on solid waste aggregate according to claim 1, characterized in that: The rubber asphalt also includes 3-6 parts by weight of polyphosphoric acid.
9. A process for preparing a self-healing rubber asphalt based on solid waste aggregates as claimed in any one of claims 1 to 8, characterized in that: The steps include: S1, in the preparatory stage, the desulfurized rubber powder is activated at 180-210°C for standby use; S2, after melting the matrix asphalt at a temperature of 160-170° C., add the desulfurized rubber powder, asphalt modifier and tackifying resin activated in step S1, and stir at a speed of 3000-4000 r / min for 20-25 min; S3. Add microcapsules, nanofillers, solid waste aggregates, mineral powder and 3-6 parts by weight of polyphosphoric acid to step S2, and continue stirring at a rotation speed of 3000-4000 r / min for 30-40 minutes to obtain rubber asphalt.
10. The process for preparing a self-healing rubber asphalt based on solid waste aggregate according to claim 9, characterized in that: The nanofiller is heated at 130-140° C. for 30 min and then added into step S3.
Citation Information
Patent Citations
Asphalt regenerant as well as preparation method and application thereof
CN105754356A
Bituminous concrete crack self-healing microcapsule and preparation method thereof
CN106495543A
High-viscosity and high-elasticity modified asphalt as well as preparation and application thereof
CN107722648A
High-viscosity modified asphalt material and preparation method thereof
CN110041720A
Modified asphalt composite particles based on waste rubber powder, and preparation method thereof
CN110256745A